Fatty acid synthase cooperates with glyoxalase 1 to protect against sugar toxicity. - Damien Garrido; Thomas Rubin; Mickael Poidevin; Brigitte Maroni; Arnaud Le Rouzic; Jean-Philippe Parvy; Jacques Montagne (PLoS Genetics, 2015)
Fatty acid (FA) metabolism is deregulated in several human diseases including metabolic syndrome, type 2 diabetes and cancers. Therefore, FA-metabolic enzymes are potential targets for drug therapy, although the consequence of these treatments must be precisely evaluated at the organismal and cellular levels. In healthy organism, synthesis of triacylglycerols (TAGs)-composed of three FA units esterified to a glycerol backbone-is increased in response to dietary sugar. Saturation in the storage and synthesis capacity of TAGs is associated with type 2 diabetes progression. Sugar toxicity likely depends on advanced-glycation-end-products (AGEs) that form through covalent bounding between amine groups and carbonyl groups of sugar or their derivatives α-oxoaldehydes. Methylglyoxal (MG) is a highly reactive α-oxoaldehyde that is derived from glycolysis through a non-enzymatic reaction. Glyoxalase 1 (Glo1) works to neutralize MG, reducing its deleterious effects. Here, we have used the power of Drosophila genetics to generate Fatty acid synthase (FASN) mutants, allowing us to investigate the consequence of this deficiency upon sugar-supplemented diets. We found that FASN mutants are lethal but can be rescued by an appropriate lipid diet. Rescued animals do not exhibit insulin resistance, are dramatically sensitive to dietary sugar and accumulate AGEs. We show that FASN and Glo1 cooperate at systemic and cell-autonomous levels to protect against sugar toxicity. We observed that the size of FASN mutant cells decreases as dietary sucrose increases. Genetic interactions at the cell-autonomous level, where glycolytic enzymes or Glo1 were manipulated in FASN mutant cells, revealed that this sugar-dependent size reduction is a direct consequence of MG-derived-AGE accumulation. In summary, our findings indicate that FASN is dispensable for cell growth if extracellular lipids are available. In contrast, FA-synthesis appears to be required to limit a cell-autonomous accumulation of MG-derived-AGEs, supporting the notion that MG is the most deleterious α-oxoaldehyde at the intracellular level.